1956
DOI: 10.6028/jres.056.045
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of cellulose in a vacuum

Abstract: Samples of cotton , cotton h ydrocelJulose, and viscose rayo n, both by t hemselves an d impreg nat;ed with sod ium carbonate or sodium chloride, were p yl'Olyzed at 250 0 to 397 0 C in a lli g h vacuum. The volatile products were fractionated a nd t he fractio ns analyzed in th e m ass spectrometer a nd by inf rared absorpt ion. Th e volatile fraction s co nsisted mainly of CO, CO2, water, and levoglucosan (tar). The residue consisted main ly of carbon (cha r).Imp reg na t ion of the cellulosic m aterials wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

1963
1963
2007
2007

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(55 citation statements)
references
References 8 publications
0
54
0
1
Order By: Relevance
“…Corresponding peaks in the three chromatograms are indicated by the same number and the products that have been identified are listed by peak number in Table XIV. A minimum of 37 different volatile products is indicated whereas earlier studies using other analytical methods have indicated from 8 to 18 products [14,16] and the recent studies on cellulose pyrolysis by isothermal gas chromatography [17,18] have indicated no more than 18 decomposition products. These results indicate the same products irrespective of the pyrolysis conditions but significant differences in product distribution are shown.…”
Section: Volatile Products From Cotton Pyrolysismentioning
confidence: 99%
“…Corresponding peaks in the three chromatograms are indicated by the same number and the products that have been identified are listed by peak number in Table XIV. A minimum of 37 different volatile products is indicated whereas earlier studies using other analytical methods have indicated from 8 to 18 products [14,16] and the recent studies on cellulose pyrolysis by isothermal gas chromatography [17,18] have indicated no more than 18 decomposition products. These results indicate the same products irrespective of the pyrolysis conditions but significant differences in product distribution are shown.…”
Section: Volatile Products From Cotton Pyrolysismentioning
confidence: 99%
“…Using the ARC, they observed this decomposition near 180°C. Madorsky et al (1956) found that cellulose decomposed, producing tars composed of levogucosan and small amounts of 1,6 anhydro-β-D-glucofuranose, 5-(hydroxymethyl)-2-furaldehyde, 2-furyl hydroxymethyl ketone, and 1,4: 3.6-dianhydro-α-D-glocopyranose; these tars were 65 wt% of the original cellulose mass. Dollimore and Hoath's (1981) review of literature on cellulose decomposition reports that over 60 secondary products have been identified.…”
Section: Thermal Behavior Of Es-31f Simulated Feed As Measured By Arcmentioning
confidence: 99%
“…The combustion of cellulose has been studied quite frequently during recent years (1)(2)(3)(4)(5)(6)(7), and several reviews have appeared (8,9). Much of the evidence strongly suggested that when the cellulose is heated, the following sequence of reactions occurs (1):…”
Section: Introductionmentioning
confidence: 99%